CASE ANALYSIS OF YOUNG MAMA (MAMAK COMPLETE URUSAN IN TREASURE OF PUSAKA) MINANGKABAU - lubis, al fikri (Jurnal Meta-Yuridis, 2018)
AbstractIndonesia, known as the motto or motto of the nation "Bhinneka tunggal ika" which means that "different but still one" from Sabang to Merauke Indonesia country has different customs or cultures in ways and behaviors that characterize each region. Minangkabau adat is basically the same as custom in other tribes of Minangkabau cultural distinctiveness with other cultures in Indonesia because Minangkabau people embrace the lineage system according to Mother or known as matrilineal. In addition, Minangkabau cultural customs regulate the distribution of inheritance harmonized with the matrilineal system so that the inheritance is left to the women. In solving a dispute related to Mamak's heritage is one of the traditional figures who participate in it, Mamak is expected as a central figure with the role of overcoming the problem of equitable division of inheritance, but instead doing the right by contradicting and selling the people's inheritance called harto pusako high (high treasures) in MinangkabauMamak is expected as a central figure with the role of overcoming the problem of equitable division of inheritance, but instead do the right otherwise by pawning and selling the inheritance of the people called harto pusako tinggi (high treasure) in Minangkabau (especially Kota Solok). In fact, many cases of Mamak have been involved in criminal law issues related to property disputes disputes, so many of them inhabit the penitentiary.This research is a research with descriptive type with qualitative approach. Therefore, this research can be used as one of the suggestions for relevant stakeholders for equitable division of heritage, and minimize the perjualbelian of the treasury itself. This research was conducted in West Sumatera Province in Solok City area. Sources of data used, namely: primary data and secondary data. Data collection techniques in this study with Observation, Interview, and Library Studies.The conclusion that can be obtained from the results of the research is the cause of the shift in the role of Mamak or deviation from the role of Mamak, among others, caused by the insistence of economic influence and globalization and the lack of musyawarah between Mamak with kemenakan in making a decision taken by Mamak so that the birth of a term Aia gadang , baraliah barn, batuka season, customs and atmosphere will barobah so that the treasure is not given for the benefit of the nephew but for the sake of his family which basically belongs to Bundo kanduang instead turns into the property of Mamak itself.Keywords: Minangkabau Adat, Role of Mamak, Heritage Treasure